Systematic review on dental caries preventive and managing strategies among type 2 diabetic patients - Chen, Haoran; Hill, Robert; Baysan, Aylin (Frontiers in Oral Health, 2022)
Purpose. The purpose of this systematic review was to evaluate current evidence to prevent and manage dental caries in patients with Type-2 diabetes mellitus (T2DM). Methods. Following PRISMA guidelines, the PICOS strategy was used to formulate a structured search. The systematic search of PubMed, Cochrane Library, MEDLINE via Ovid, EMBASE, Scopus, Web of Science, Lilacs without any date limit and/or language restrictions. Two independent reviewers performed data extraction and risk of bias assessments in the included studies. Data homogeneity was assessed according to interventions for treating dental caries in T2DM. Statistical analyses were performed with JMP®. Results. Two studies out of 909 were included in the systematic review. Only quantitative studies involving topical applications for management of dental caries in patients with T2DM were included. One study assessed the effect of intensive oral hygiene care program including toothbrushing and interdental cleaning using interproximal brushes and/or dental floss, supragingival debridement by dental hygienist with educational brochures in T2DM, whilst another investigated the immunologically active salivary substitutes with using Oral Hygiene Instructions (OHI), mouthwash and moisturizing gel for six months. intensive oral hygiene care program or immunologically active salivary substitutes with using OHI, mouthwash and moisturizing gel for six months were reported to reverse/arrest dental caries in patients with T2DM. Conclusion. The current randomized controlled clinical trials demonstrated that regular extensive oral health education using interdental cleaning aids, mouthwash, moistening gel and saliva substitutes including lactoperoxidase, lysozyme, glucose oxidase and lactoferrin could control oral inflammation and contribute to the management of dental caries in patients with T2DM.